2001
DOI: 10.1016/s0370-1573(00)00139-3
|View full text |Cite
|
Sign up to set email alerts
|

Superfluid analogies of cosmological phenomena

Abstract: Superfluid 3He-A gives example of how chirality, Weyl fermions, gauge fields and gravity appear in low energy corner together with corresponding symmetries, including Lorentz symmetry and local SU(N). This supports idea that quantum field theory (Standard Model or GUT) is effective theory describing low-energy phenomena. * Momentum space topology of fermionic vacuum provides topological stability of universality class of systems, where above properties appear. * BCS scheme for 3He-A incorporates both ``relativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
359
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(368 citation statements)
references
References 184 publications
(591 reference statements)
7
359
1
1
Order By: Relevance
“…[35]. This is consistent with a quite general argument that the transformation properties for quasiparticles in the lowenergy effective theories should not depend on the quantities such as the bare particle mass m. [48] As a by-product of this transformation law, the Bogoliubov-quasiparticle current j is invariant under Galilean boosts, which is also consistent with the invariance of the quasiparticle momentum.…”
Section: Symmetry-based Effective Lagrangiansupporting
confidence: 81%
See 2 more Smart Citations
“…[35]. This is consistent with a quite general argument that the transformation properties for quasiparticles in the lowenergy effective theories should not depend on the quantities such as the bare particle mass m. [48] As a by-product of this transformation law, the Bogoliubov-quasiparticle current j is invariant under Galilean boosts, which is also consistent with the invariance of the quasiparticle momentum.…”
Section: Symmetry-based Effective Lagrangiansupporting
confidence: 81%
“…In what follows, we employ formula (48) to determine the superfluid (number) density n s = ρ s /(m ↑ + m ↓ ) at zero temperature in the special case of an equal mass system of interest in the present work.…”
Section: Superfluid Density Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, it can be shown by using the equations of motion obtained from the free energy (1) that for most potentials V , which are approximately invariant under the U (2) symmetry, it is impossible for the ψ 2 field to remain constant when the ψ 1 field varies in space. On the other hand, from the energetic point of view, given that the potential V can be written approximately as V ≈ U (|ψ 1 | 2 + |ψ 2 | 2 ), one can argue (in part based on previous work [5,6,7,8,9,10,11]) that it is favorable for the ψ 2 field to increase its magnitude in the vortex core to compensate the decrease in the magnitude of ψ 1 . So, anticipating a non-trivial behavior of the neutron field ψ 2 , let's adopt the following cylindrically symmetric ansatz for the fields describing a proton vortex with a unit winding number:…”
Section: Structure Of Magnetic Flux Tubesmentioning
confidence: 99%
“…Similar methods were employed to investigate the same phenomenon in the context of black hole physics [5,6]. These modifications were inspired by higher dimensional models of the universe [7] or from condensed matter analogs of gravity [8]. It was shown that the prediction of a thermal Hawking spectrum is insensitive to modifications of the physics at the trans-Planckian end of the spectrum.…”
Section: Introductionmentioning
confidence: 99%